Anesthetic and analgesic approach in total knee arthroplasty: A national survey study (Annals of Medical Research, 2021)
Aim: Although the optimum anesthetics and analgesic choice for total knee arthroplasty is a heavily debated topic in recent years, the failure to reach any ideal consensus on this topic leads clinicians to adopt different approaches. This study was conducted to assess differences in general anesthetic and analgesic approaches toward the total knee arthroplasty across Turkey.Materials and Methods: Our 28-item survey was presented online to physicians who work as Anesthesiology and Reanimation specialists in Turkey and agreed to participate in the study. The survey includes questions about the techniques preferred by the clinicians in the management of anesthesia and postoperative analgesia in TKA and the main reasons underlying their preferences.Results: 255 anesthesiologists, i.e. 72 (28.1%) faculty members and 183 (71.9%) specialists, completed the study in full. According to our survey, spinal anesthesia (61.3%) comes first in the selection of an anesthetic method in TKA, followed by the Combined Spinal-Epidural Anesthesia (32.4%). The spinal anesthesia is the most frequently preferred method in training and state hospitals and Combined Spinal-Epidural Anesthesia is the most frequently preferred method in private hospitals. The use of peripheral nerve blocks is 49.8% (127). Femoral nerve block is preferred with 79.7%, followed by adductor canal block with 36.1%. The rate of use of intravenous patient-controlled analgesia is 38.1% and the most commonly preferred analgesia is Tramadol (69.1%). 63.1% of those using epidural anesthesia do not use any epidural patient-controlled analgesia device. The physicians reported that the lack of a team to follow up epidural patient-controlled analgesia device (50.9%) as the most common reason for not choosing epidural patient-controlled analgesia.Conclusion: Regional anesthesia is the first preference in the anesthesia management of total knee arthroplasty in our country. In postoperative analgesia practice, peripheral nerve blocks are preferred at a higher rate than epidural and intravenous patient controlled analgesia.
Keywords: Anesthesia; postoperative analgesia; total knee artroplasthy